Who owns the roads? How motorised traffic discourages walking and bicycling. Issue 6 (3rd December 2009) - Jacobsen, P L; Racioppi, F; Rutter, H
Abstract : Objective: To examine the impact of traffic on levels of walking and bicycling. Method: Review of the literature of medical, public health, city planning, public administration and traffic engineering. Results: The real and perceived danger and discomfort imposed by traffic discourage walking and bicycling. Accurately or not, pedestrians and bicyclists judge injury risk and respond accordingly. Although it can be difficult to measure these effects, observed behaviour provides good evidence for these effects, with the strongest association being an inverse correlation between volumes and speeds of traffic and levels of walking and cycling. Conclusion: Interventions to reduce traffic speed and volume are likely to promote walking and bicycling and thus result in public health gains.